2005
DOI: 10.1183/09031936.05.00082004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the cues used by patients when making assessments of their asthma severity

Abstract: This study measured the relative contribution of four cues: symptoms, effect on activities, emotions and social life, to patients' judgments of overall asthma severity.Judgement analysis techniques were applied to patients' assessments of overall asthma severity using asthma states described in scenarios based on these cues.Altogether, 40 patients, mean age 52 yrs, mean forced expiratory volume in one second 67% predicted, were studied. The relative importance of the cues varied widely between patients; sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…When rating Acceptable health, different factors may have been important to different patients. This view is also supported by our previous work that showed that the factors that patients consider when assessing their global asthma severity vary between individuals (11). Some patients rely mainly on symptoms, whereas others take a number of factors into account.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…When rating Acceptable health, different factors may have been important to different patients. This view is also supported by our previous work that showed that the factors that patients consider when assessing their global asthma severity vary between individuals (11). Some patients rely mainly on symptoms, whereas others take a number of factors into account.…”
Section: Discussionsupporting
confidence: 54%
“…Global questions measure a broad, undefined concept that allows for wide variation in how individuals interpret and respond to them (11). By contrast, items included in a disease-specific, health-related quality-of-life questionnaire are very specific and prompt patients to consider their health in a particular and standardized way.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, we propose that Borg and VAS ratings may represent a very different sensation than "breathlessness" for African American asthmatics (8,9). If African Americans and Whites do interpret the terminology, or words, on the Borg and VAS differently then under or over treatment of asthma symptoms may occur (34,36). Few studies, if any, have examined how other ethnic groups interpret the words on the Borg and VAS; this possible bias may limit the interpretation of our Borg and VA study results.…”
Section: Discussionmentioning
confidence: 97%
“…These descriptors may provide insights into how asthmatics code the severity of their symptoms and then decide whether or not to treat a particular symptom. It is well accepted that how an asthmatic patient rates his or her symptom severity during any given acute asthma episode varies widely (13,36,37). Because multiple pathophysiological mechanisms are associated with asthma, it is only logical that symptom perception would also be highly variable (3,5).…”
Section: Discussionmentioning
confidence: 98%